Evaluation of sperm motility and velocity of different genetic groups of bucks using Computer-Assisted Sperm Analyzer - Islam, MR; Talukder, MKU; Rahman, MS; Husain, SS (Bangladesh Journal of Animal Science, 2020)
Semen quality assessment is a prime prerequisite for any breeding programme. Computer-Assisted Sperm Analyzer (CASA) can measure the semen quality very accurately and sharply. The research was conducted at American Dairy Limited (ADL) at Vangnahati, Sreepur, Gazipur. A total of 120 ejaculates were collected from three genetic groups of bucks namely Black Bengal (BB), Boer and Jamunapari (JP) with a view to characterize and compare the semen motility and velocity parameters using Computer- Assisted Sperm Analyser. Significantly (p<0.05) higher ejaculate volume was found in Boer buck (1.73±0.16 ml) with the lower in BB buck (0.98±0.14), respectively. But significantly (p<0.05) higher total, forward progressive and fast motility was found in BB (55.47±3.17, 47.23±2.74 and 37.62±2.40%) and lower in JP (40.67±3.37, 30.97±2.91 and 21.81±2.55%), respectively. Significantly (p<0.01) fastest straight line and average path distance was observed in Boer bucks (12.29±1.63 and 15.89±1.95 μm) than Black Bengal and Jamunapari bucks (4.38±1.19 and 7.26±1.57; and 3.14±1.27 and 8.42±1.95 μm), respectively. The distance curved line (DCL) and distance straight line (DSL) was significantly (p<0.05) higher in Boer (29.13±4.87, 12.29±1.63 and 15.89±1.95 _m/sec) and lower in BB (22.07±4.36 and 7.26±1.57 _m/sec), respectively. In case of curvilinear velocity, straight line velocity and average path velocity value was significantly (p<0.01) higher in Boer (127.08±13.88, 50.01±7.68 and 68.13±7.25 _m/sec) with lower in JP (62.01±12.77, 15.75±7.35 and 22.39±9.42) where as linearity and straightness was higher in Boer and lower in BB (p>0.05), respectively. The scrotal circumference had positive correlations with semen volume and curvilinear velocity for all the genotypes. It was concluded that semen of Boer bucks found consistently better than other two genetic groups of bucks. Further, competitive studies with large sample may be performed to evaluate the breed specific differences in available goat breeds. I think this study also disclosed the some rare parameters of semen quality by using Computer-Assisted Sperm Analyzer which was impossible in manually. These results of the present study could be an authentic guideline in future performance tests of different genetic groups of bucks. Bang. J. Anim. Sci. 2019. 48 (2): 67-74